Prevalence of erm Gene among Clinical Isolates of Staphylococcus aureus in Shahrekord, Iran - Kourosh Naderi; Fahimeh Ghanbari; Farzad Khademi; Behnam Zamanzad (Journal of Kerman University of Medical Sciences, 2018)
Background: Development of drug resistance to Staphylococcus aureus (S. aureus) has led to the use of older antibiotics such as macrolide-lincosamide-streptogramin B (MLSB) for the treatment of infections. MLSB resistance can be caused by several mechanisms, however, one of the predominant reasons is target modification mediated by erm genes. The objective of this study is to determine the prevalence of erm genes and the frequency of constitutive MLSB (cMLSB), inducible MLSB (iMLSB), and MS phenotypes using D-test and polymerase chain reaction (PCR) methods. Methods:D-test was performed on 110 clinical specimens of S. aureus collected from Kashani and Hajar Hospitals in Shahrkord from October 2014 to May 2015. After sampling, DNA extraction was performed by simple boiling method and, in order to detect erm genes, multiplex PCR was carried out on erythromycin resistant isolates using specific primers. Results:The result of this study revealed that among 110 S. aureus isolates examined, 35 (31.8%) were MRSA and frequency of cMLSB, iMLSB, and MS resistant phenotypes were 22 (20%), 9 (8.2%), and 2 (1.8%), respectively. The genes ermA, ermB, and ermC were detected in 27 (24.5%), 28 (25.4%), and 26 (23.6%) isolates. Conclusion:This study demonstrated that cMLSB was the most common phenotype among isolated S. aureus. Moreover, another interesting point to notice in our study was the high frequency of the ermB gene in iMLSB resistant phenotypes.